(untitled) (Journal of the College of Basic Education, 2022)
In this study, the efficacy of each of the aqueous extract and the alcoholic extract was tested at an effective dose of 100 mg/kg of body weight on the level of glucose, cholesterol and triglycerides in the blood serum of healthy male rabbits with experimental diabetes induced by Alloxan and compared the results with the drug Glibenclamid. The study showed the ability of the aqueous and alcoholic extracts of the mint plant both to cause a significant decrease and return to the normal limit for all the studied variables compared with the untreated healthy control groups effectively, which led to the conclusion that more studies can be conducted to choose the effectiveness of the extracts of the mint plant and to examine its toxicity on tissues to confirm There are no side effects during continuous use.